2017
DOI: 10.1073/pnas.1707792114
|View full text |Cite|
|
Sign up to set email alerts
|

Mycobacterium tuberculosisis protected from NADPH oxidase and LC3-associated phagocytosis by the LCP protein CpsA

Abstract: ' success as a pathogen comes from its ability to evade degradation by macrophages. Normally macrophages clear microorganisms that activate pathogen-recognition receptors (PRRs) through a lysosomal-trafficking pathway called "LC3-associated phagocytosis" (LAP). Although activates numerous PRRs, for reasons that are poorly understood LAP does not substantially contribute to control. LAP depends upon reactive oxygen species (ROS) generated by NADPH oxidase, but fails to generate a robust oxidative response. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
148
4
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(185 citation statements)
references
References 69 publications
9
148
4
2
Order By: Relevance
“…Other mechanisms contribute to M. tuberculosis innate immunity, including pattern recognition molecules and adaptors (Stamm et al, 2015), neutrophils (Blomgran et al, 2012; Blom-gran and Ernst, 2011), reactive oxygen (Köister et al, 2017) and nitrogen (Mishra et al, 2017), autophagy (Ouimet et al, 2016), and apoptosis (Martin et al, 2012). For each of these, M. tuberculosis has evolved the ability to inhibit or resist these defense mechanisms (Cambier et al, 2014; Goldberg et al, 2014).…”
Section: Mechanisms Of Immunity That Control M Tuberculosismentioning
confidence: 99%
“…Other mechanisms contribute to M. tuberculosis innate immunity, including pattern recognition molecules and adaptors (Stamm et al, 2015), neutrophils (Blomgran et al, 2012; Blom-gran and Ernst, 2011), reactive oxygen (Köister et al, 2017) and nitrogen (Mishra et al, 2017), autophagy (Ouimet et al, 2016), and apoptosis (Martin et al, 2012). For each of these, M. tuberculosis has evolved the ability to inhibit or resist these defense mechanisms (Cambier et al, 2014; Goldberg et al, 2014).…”
Section: Mechanisms Of Immunity That Control M Tuberculosismentioning
confidence: 99%
“…Our present data support the uptake of EVs by macrophages and DCs but not T cells or neutrophils when administered by intratracheal injection (Fig EV4). Targeting mycobacterial PAMPs and antigens into M.tb ‐infected macrophages or uninfected host cells may trigger anti‐mycobacterial pathways such as LAP and provide M.tb antigens for activation of an acquired immune response . We found that EVs containing M.tb PAMPs such as mycobacterial RNA are able to elicit an effective anti‐mycobacterial response in macrophages.…”
Section: Discussionmentioning
confidence: 85%
“…Unlike classical autophagy, LAP is a Ubindependent process and only utilizes a subset of autophagy machinery components for the modification of microbe-containing vesicles by the LC3-conjugation system [27,28]. As an established intracellular bacterial pathogen, M.tb has evolved an inhibitory mechanism for evading LAP through release of CpsA, a LytR-CpsA-Psr (LCP) domain-containing protein that may interfere with the recruitment of NOX2 NADPH oxidase to M.tb-containing phagosomes [29]. Nevertheless, our data indicate that this M.tb-mediated inhibition can be overcome by treating infected macrophages with EVs isolated from M.tb-infected macrophages and IFN-c.…”
Section: Intra-tracheal Ev Administrationmentioning
confidence: 99%
“…Unlike classical autophagy, LAP is a Ub-independent process and only utilizes a subset of autophagy machinery components for the modification of microbecontaining vesicles by the LC3-conjugation system (Lam et al, 2013;Hubber et al, 2017). As an established intracellular bacterial pathogen, M.tb has evolved an inhibitory mechanism for evading LAP through release of CpsA, a LytR-CpsA-Psr (LCP) domain-containing protein that may interfere with the recruitment of NOX2 NADPH oxidase to M.tb-containing phagosomes (Köster et al, 2017). Interestingly, EVs-mediated LC3 conjugation of M.tb-containing phagosomes requires the host RIG-I/MAVS cytosolic RNA sensing pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the agents investigated previously, the EVs derived from M.tb-infected host cells will have a more limited target cell population as prior studies indicate a predisposition for EV uptake by macrophage and DCs (Bhatnagar et al, 2007). Targeting mycobacterial PAMPs and antigens into M.tb-infected macrophages or uninfected host cells may trigger antimycobacterial pathways such as LAP as well provide M.tb antigens for activation of an acquired immune response (Bhatnagar et al, 2007;Köster et al, 2017). We found that EVs containing M.tb PAMPs such as mycobacterial RNA are able to elicit an effective antimycobacterial response in macrophages.…”
Section: Discussionmentioning
confidence: 99%